Peritoneal Dialysis Use and Practice Patterns: An International Survey Study - Cho, Yeoungjee; Bello, Aminu K; Levin, Adeera; Lunney, Meaghan; Osman, Mohamed A; Ye, Feng; Ashuntantang, Gloria E; Bellorin-Font, Ezequiel; Gharbi, Mohammed Benghanem; Davison, Sara N; Ghnaimat, Mohammad; Harden, Paul; et al. (American journal of kidney diseases, 2021)
RATIONALE & OBJECTIVE: Approximately 11% of people with kidney failure worldwide are treated with peritoneal dialysis (PD). This study examined PD use and practice patterns across the globe. STUDY DESIGN: A cross-sectional survey. SETTING & PARTICIPANTS: Stakeholders including clinicians, policy makers, and patient representatives in 182 countries convened by the International Society of Nephrology between July and September 2018. OUTCOMES: PD use, availability, accessibility, affordability, delivery, and reporting of quality outcome measures. ANALYTICAL APPROACH: Descriptive statistics. RESULTS: Responses were received from 88% (n=160) of countries and there were 313 participants (257 nephrologists [82%], 22 non-nephrologist physicians [7%], 6 other health professionals [2%], 17 administrators/policy makers/civil servants [5%], and 11 others [4%]). 85% (n=156) of countries responded to questions about PD. Median PD use was 38.1 per million population. PD was not available in 30 of the 156 (19%) countries responding to PD-related questions, particularly in countries in Africa (20/41) and low-income countries (15/22). In 69% of countries, PD was the initial dialysis modality for≤10% of patients with newly diagnosed kidney failure. Patients receiving PD were expected to pay 1% to 25% of treatment costs, and higher (>75%) copayments (out-of-pocket expenses incurred by patients) were more common in South Asia and low-income countries. Average exchange volumes were adequate (defined as 3-4 exchanges per day or the equivalent for automated PD) in 72% of countries. PD quality outcome monitoring and reporting were variable. Most countries did not measure patient-reported PD outcomes. LIMITATIONS: Low responses from policy makers; limited ability to provide more in-depth explanations underpinning outcomes from each country due to lack of granular data; lack of objective data. CONCLUSIONS: Large inter- and intraregional disparities exist in PD availability, accessibility, affordability, delivery, and reporting of quality outcome measures around the world, with the greatest gaps observed in Africa and South Asia.
Keywords: peritoneální dialýza; access to health care; health care disparities; lékařská praxe - způsoby provádění; zdravotní politika; průzkumy a dotazníky; chronické selhání ledvin; nefrologové; hodnocení výsledků péče pacientem; Health Services Accessibility; správní úředníci; průřezové studie; Surveys and Questionnaires; global survey; Quality of Health Care; dostupnost zdravotnických služeb; lékaři; Peritoneal Dialysis; Internationality; lidé; Outcome Assessment, Health Care; Patient Reported Outcome Measures; hodnocení výsledků zdravotní péče; health care delivery; internacionalita; affordability of health care; vyspělé země; Physicians; RRT modality; Kidney Failure, Chronic; Epidemiology; poskytování zdravotní péče; Delivery of Health Care; Health Policy; výdaje na zdravotnictví; home dialysis; Nephrology; peritoneal dialysis (PD); Cross-Sectional Studies; end-stage renal disease (ESRD); náklady a analýza nákladů; health policy; podíl na nákladech; Developing Countries; Nephrologists; renal replacement therapy (RRT); rozvojové země; kidney failure; Practice Patterns, Physicians'; international differences; nefrologie; Administrative Personnel; Cost Sharing; kvalita zdravotní péče; Health Expenditures; Developed Countries; Costs and Cost Analysis; Humans